Efektivitas Keberhasilan Dakwah Ustadz Hanan Attaki Melalui Sosial Media Tiktok - Hermaya, Azzahra Putri; Khatibah, Khatibah (Jurnal Cendekia Media Komunikasi Penelitian dan Pengembangan Pendidikan Islam, 2024)
This study evaluates the efficacy of the da'wah message disseminated by Ustadz Hanan Attaki through the TikTok social media platform. Ustadz Hanan chose TikTok as the platform to disseminate his da'wah to a broader audience, particularly the youth. This research employed a mixed-methodologies approach, utilizing quantitative methods through case studies and purposive sampling procedures with 80 respondents. Quantitative investigation indicates that the R square value is 25.9%, signifying that 25.9% of preaching efficiency is affected by TikTok social media, whereas other factors determine 74.1%. The hypothesis test findings indicate a calculated t-value of 5.219, exceeding the t-table value of 2.375, with a significance level of 0.00 < 0.05, demonstrating a positive and substantial impact of TikTok on the efficacy of da'wah. In the qualitative component, comprehensive interviews were performed with multiple followers of Ustadz Hanan Attaki on TikTok to gain deeper insights into their experiences and impressions of the imparted da'wah messages. Qualitative findings indicate that a delivery style pertinent to daily life and the utilization of accessible language are critical elements influencing the efficacy of da'wah. This research demonstrates that TikTok is an excellent medium for disseminating da'wah, particularly among younger demographics, and significantly impacts the audience's comprehension and reaction to the da'wah message. This study enhances the body of knowledge regarding digital da'wah and social media, particularly concerning the efficacy of da'wah in the digital age.